Awareness of clinical application of vitamin E among dental students. - E, Nandakumar.; Ganapathy, Dhanraj; Kumar Pandurangan, Kiran; Velayudhan, Ashok (International Journal of Psychosocial Rehabilitation, 2020)
BACKGROUND: Vitamin E is a major cutaneous, non-enzymatic antioxidant, scavenging free radicals generated through a variety of mechanisms leading to skin pathology. Vitamin E is also anti-inflammatory, asdemonstrated in numerous animal models Only two forms ofvitamin E exist in the body: α-tocopherol and γ-tocopherol. Both occur in abundance within the stratum corneum after their secretionby sebaceous glands. The increased density of vitamin Ewithin the stratum corneum preserves the integrity and barrierfunction of the skin while protecting the most superficial cutaneouslayer from oxidationSupplementation of vitamin E, orally orintravenously, has been shown to reach the outermost portions of the skin and does so within two weeks of supplementation. The aim of the study was to evaluate and compare the awareness of clinical application of vitamin E among dental students. A cross-sectional survey was carried among 100 dental practitioners using a questionnaire. Questionnairecontained 10 questions on awareness of clinical applications of vitamin E among dental students. The data were extracted and analyzed. In conclusion, the availability of very sensitive methods for measuring concentrations of fat-soluble vitamins has made it feasible to examine these vitamins in small plasma samples from preterm infants. Although the usage of dietary supplements of vitamin E is high in students, there is a dearth of knowledge, especially regarding the role of micronutrients in health and disease.